Arthrodesis of Ipsilateral Hallux Metatarsophalangeal and Interphalangeal Joints. Issue 1 (25th January 2021) - Brodsky, James W.; Zide, Jacob R.; Kim, Kim Eung Soo; Charlick, Daniel A.; Daoud, Yahya; Bohl, Daniel D.
Background: Arthrodesis of the ipsilateral hallux metatarsophalangeal (MTP) and interphalangeal (IP) joints may be required for severe arthritis or deformity at both joints. The purpose of this study was to review outcomes of ipsilateral first MTP and IP joint arthrodesis. Methods: Twenty feet were identified, for which the diagnosis was rheumatoid arthritis in 14, failed hallux valgus surgery in 5, and hallux rigidus in 1. The IP arthrodesis was performed first in 6 feet; MTP first in 8 feet; and both joints simultaneously in 6 feet. Median follow-up was 28 months (range 12-94). Medical records and radiographs were reviewed. American Orthopaedic Foot & Ankle Society (AOFAS) score and patient satisfaction were determined. Results: Although all of the MTP arthrodeses healed, 8 of 20 feet (40%) failed to heal at the IP arthrodesis. The rate of IP nonunion was 17% (1/6) with IP arthrodesis first, 50% (4/8) with MTP arthrodesis first, and 50% (3/6) with simultaneous arthrodesis. Four of 8 IP nonunions were symptomatic. Subsequent surgery was required in 11 feet (55%), including repair of IP nonunion in 3 feet, hardware removal in 4, revision MTP malunion in 2, wound debridement in 1, and soft tissue reconstruction in 1. Median hallux AOFAS score for the cohort increased from 25 to 68. Eighteen feet resulted in patients who were very satisfied or satisfied with minor reservations. Neither AOFAS score nor satisfaction trended toward association with IP union. Conclusion: Ipsilateral arthrodesis of the hallux MTP and IP joints was challenging because of high rates of reoperation and IP nonunion, the latter of which was likely related to increased mechanical stress on the IP joint with immobilization of the MTP joint. Despite the high IP nonunion rate, IP nonunion did not predict patient-reported outcome. Fibrous ankylosis was an acceptable clinical outcome in many cases. Level of Evidence: Level IV, case series.